2006
DOI: 10.1002/sce.20193
|View full text |Cite
|
Sign up to set email alerts
|

Teaching science in museums: The pedagogy and goals of museum educators

Abstract: Museum educators have a longstanding presence in museums and play a significant role in the institutions' educational agenda. However, research on field trips to science museums has predominantly explored teachers' and students' perspectives with little acknowledgment of the museum educators who develop and implement the educational programs the students experience. This study sought to describe instruction undertaken in, and goals driving, science museums' lessons through observations of museum educators foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
14

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(77 citation statements)
references
References 27 publications
3
60
0
14
Order By: Relevance
“…A study of the pedagogical actions and rationales of educators reported that the design of their programmes and the patterns of their discourse resembled schoolteachers' practice [30]. Interviews with educators about their pedagogical decisions and reasoning revealed a complexity in science pedagogy in museums, which challenged existing depictions of didacticism and inattentive to learners as suggested by previous research [7], [28].…”
Section: Diversity Of Educational Responsibilities and Languagementioning
confidence: 87%
“…A study of the pedagogical actions and rationales of educators reported that the design of their programmes and the patterns of their discourse resembled schoolteachers' practice [30]. Interviews with educators about their pedagogical decisions and reasoning revealed a complexity in science pedagogy in museums, which challenged existing depictions of didacticism and inattentive to learners as suggested by previous research [7], [28].…”
Section: Diversity Of Educational Responsibilities and Languagementioning
confidence: 87%
“…Lynn: In addition to Jen's point, research on how educators in museums teach science to visitors (primarily schoolchildren) describes their practice and models of the communicative process as transmissionist (Tran 2007). I would argue that, in this case, it is not an emotional defense mechanism, which drives transmissive teaching.…”
Section: Issues Of Power Emotions and Learningmentioning
confidence: 96%
“…The United States cannot claim that museum educators are all formally trained educators either even though there is more evidence of museum programs having the same characteristics as a formal lesson. Tran's (2007) research on the pedagogy and goals of museum educators demonstrates that museum educators in the U.S. are interested in designing museum classes for field trips that inspire interest in science and learning. Their perspective is that students experience the museum class as part of a continuum of experiences as opposed to one-shot deals.…”
Section: The Role Of Museum Educatorsmentioning
confidence: 98%